Nepal’s Armed Conflict and the Peace Process - Tiwari, Ram Krishna (Tribhuvan University Journal, 2013)
This paper deals with the political development of Nepal and its history of armed conflict. The formation of Nepali nation-state is not very long, again throughout its political history Nepal remained an independent country, but this country experienced a decade long political conflict from 1996 to 2006. The failure of political change of 1951 and 1990 prepared a political ground for the official beginning the People’s War, and after 2006 the country is moving into the path of peace process. Similarly, the formation of political parties has not a long history compared it with the beginning of democratic movement in India, China and other countries of the world. The poor political vision of the political leaders failed to institutionalize the political change of Nepal, and now the ongoing peace process of Nepal should erase all the weaknesses and conclude it for building prosperous nation.